Rhinos at recess eaudiobook - Osborne, Mary Pope (Magic Tree House, 2023)
The #1 bestselling Magic Tree House series is ready to whisk you away across the world with Jack and Annie—this time to the African savanna! Jack and Annie are on the playground at recess when they feel the magic tree house calling them. They sneak away and are whisked off on an adventure in South Africa, where a majestic rhino needs saving!  There are a swooping helicopter, strict park rangers, and—most terrifying of all—poachers. How do you hide one of the largest land mammals in the flat terrain of the African savanna? Jack and Annie are going to need a little bit of magic for this mission! Did you know that there's a Magic Tree House book for every kid? Magic Tree House: Perfect for readers who are just beginning chapter books Merlin Missions: More challenging adventures for the experienced reader Fact Trackers: Nonfiction companions to your favorite Magic Tree House adventures If you're looking for Merlin Mission #37: Dragon of the Red Dawn , it was renumbered as Merlin Mission #9 when the series was rebranded in 2017.